Simulated ocean acidification affects shark tooth morphology - Baum, Maximilian; Haussecker, Timo; Walenciak, Oliver; Köhler, Steffen; Bridges, Christopher R.; Fraune, Sebastian (Frontiers in Marine Science, 2025)
Changing ecological factors pose a challenge to many organisms. Global changes and the associated environmental changes have major impacts on marine organisms and threaten the biodiversity of marine ecosystems. It has been shown in previous experimental studies that ocean acidification caused by anthropogenic CO2 release into the atmosphere and subsequent dissolution in seawater will have a significant impact on various marine organisms. Here, we investigated the corrosive effects from acidification on the morphology of isolated shark teeth in an eight-week incubation at a pH of 7.3, the expected seawater pH in the year 2300. The typical littoral blacktip reef shark (Carcharhinus melanopterus), which is often kept in display aquaria under controlled conditions, has been used for this purpose, greatly facilitating minimally invasive sampling for in-situ investigation. The teeth of this typical Requiem Shark species are orthodont teeth, which show strong serration in the teeth of the upper jaw. Using scanning electron microscopy (SEM) we could observe the corrosive effects of acidification on the different tooth structures, such as the root, primary and secondary serrations and the crown of the blacktip reef sharks teeth. Our results show that ocean acidification will have significant effects on the morphological properties of teeth, including visible corrosion on the crown, degradation of root structures, and loss of fine serration details under low pH conditions which could lead to changes in foraging efficiency, energy uptake, and ultimately elasmobranch fitness in future oceans.